The Impact of Housing Loans on Residents' Happiness - Guo, Shuo (International Journal of Social Sciences and Public Administration, 2024)
A home purchase loan refers to a loan that a home buyer applies for to a bank or any other financial institution to buy a home. As people's yearning for a better life increases, more and more people are more inclined to buy houses, thus generating loans for house purchases. With the increase of housing loans, residents' happiness is facing new challenges. This paper analyzes the main composition of housing loan, and explores the impact of housing loan on residents' happiness through the data tracking of different families. The results show that housing loans have a significant impact on residents' happiness. First, housing loans, as an economic burden, may have a negative impact on residents' well-being. However, on the other hand, housing loans may also have a positive impact on residents' well-being. Having a home is an important part of how many people achieve a stable life, which may give them satisfaction and security, which are the main reasons for determining whether it is significant or not. This paper also determines the credibility of the data results through mechanism test, heterogeneity analysis and robustness analysis.